STRATEGI KENDALI ORGANISASI COFFEE SHOP DALAM MENINGKATKAN KUALITAS PRODUK TERHADAP MINAT PELANGGAN (Studi Kasus Team Kinerja “TALK BOGOR”) - Salomon A.M. Babys; Raden Cahyo Prabowo (FISIP Universitas Bung Karno, 2021)
Abstract The increasing role of the coffee industry is accompanied by a rapid increase in the demand for coffee. It is observed that it has a weakness in the amount of coffee capacity which is still not evenly distributed and is not able to meet the existing demand in Indonesia. There are challenges for companies to survive and renew their competitive strategies. This study aims to find out the competitive strategy applied by the company today and try to formulate the company's blue ocean competitive strategy. In collecting data using interview and observation methods. Determination of interview sources using purposive sampling technique. The data obtained was then tested for the validity of the data using source triangulation. Research on the Coffee Shop Organizational Strategy in team performance Quality Against Customer Interests (Case Study of the